Special nutrition problems of the elderly (Los Angeles: National Health Video, 1997)
(Producer) This video covers malnutrition, obesity, protein-calorie malnutrition, chewing problems, alcoholism, drug-food interactions, constipation, iron deficiency, dehydration, eating alone and lonely eating. It encourages physical activity to maintain overall good health.
Videocassettes is available at Koleksi Media, Perpustakaan HUKM
Keywords: Nutrition -- vidoecassettes; Nutrion Disorders -- prevention and control -- videocassettes; Digestive Physiology -- videocassettes; Diet -- videocassettes; Aged -- videocassettes